Carthamus tinctorius Linn. Reduce Blood Pressure and Oxidative Stress Markers in Nitric Oxide-Deficient Hypertensive Rats - Prasattong, Patoomporn; Pakdeechote, Poungrat; Kukongviriyapan, Upa; Prachaney, Parichat; Tangsujarit, Panot (Srinagarind Medical Journal, 2014)
Background and Objective: Carthamus tinctorius L. (CT) has been reported to have antioxidant, anti-inflammatory and antidiabetic effects. Nω-Nitro-L-arginine methyl ester (L-NAME)-induced hypertension in rats was reported to increased reactive oxygen species. This study aimed to investigate whether CT extract could reduce blood pressure and oxidative stress markers in L-NAME hypertensive rats. Methods: Male Sprague-Dawley rats, weighing 230-260 g were divided into three groups. 1) Normal control group, 2) L-NAME control group and 3) L-NAME+CT extract group (n=6,each). Normotensive rats received drinking water for five weeks and vehicle for the last two weeks. Hypertensive rats received L-NAME (40 mg/kg/day) and vehicle or CT extract (500 mg/kg/day) for the last two weeks. Systolic blood pressure (SP) was monitored using tail cuff method once a week. At the end of study blood pressure, heart rate (HR), hindlimb blood flow (HBF) and hindlimb vascular resistance (HVR) were measured. Superoxide production in carotid arteries and plasma malondialdehyde (MDA) were detected. Results: Daily administration of L-NAME for five weeks showed significant increases in BP, HVR and decreased HBF. Furthermore, increases in vascular superoxide production and plasma MDA were observed in hypertensive rats (p<0.05). CT extract significantly reduced BP, HVR, and significantly increased HBF in hypertensive rats (p<0.05). Additionally, oxidative stress markers were reduced in hypertensive rats treated with CT extract. Conclusions: The present investigation suggests that CT extract exhibited an antihypertensive effect. This might be related with its antioxidant capacity.